Mining legume germplasm for genetic gains: An Indian perspective - Gayacharan,; Parida, Swarup K.; Mondal, Nupur; Yadav, Rashmi; Vishwakarma, Harinder; Rana, Jai C. (Frontiers in Genetics, 2023)
Legume crops play a significant role in food and nutritional security and help in environmental sustainability. Despite legumes being highly beneficial crops, their yield and production could not be enhanced to a satisfactory level. Amid rising population, per capita average legume food grain consumption in India has reduced by 71% over the last 50 years, that has led to protein related malnutrition in large segment of Indian population, especially women and children. Proneness to diseases and pests, lack of good ideotypes, less amenability for mechanization, less responsiveness to fertilizer inputs and poor genetic base are the major bottlenecks hindering the yield enhancement in grain legumes. Globally, around 0.4 million ex situ collections of legumes are conserved worldwide, which need to be mined for identification of ideal donors for various traits. Indian National Genebank conserves over 63,000 accessions of legumes belonging to 61 species. The recent initiatives in the direction of unlocking the genetic potential of ex situ collections, large-scale germplasm characterization and evaluation are being done. So far >200 accessions of various legumes have been registered as unique donors. This large-scale phenotyping has also been integrated with omics sciences for more targeted and focused trait/ gene discovery and their use for enhancing genetic gains. Also, wherever the genetic base of major legumes is narrow, wild relatives have been evaluated, and these are being used through pre-breeding. We assume that these useful genes and traits identified for various traits will be used in breeding legumes for enhanced production, quality, and climate resilience.